‘The company will fire you because you are too expensive’: a photo-ethnography of health care rights among Filipino migrant seafarers - Shannon Guillot-Wright (Springer Nature, 2021)
Abstract With fatal injuries six times the rate of all US occupations, people who live and work at sea are part of one of the most dangerous occupations. Few ships have health care workers aboard despite many seafarers being at sea for months. While seafarers are guaranteed a right to health care through maritime labor laws and conventions, it is unclear whether or how they access these rights. Therefore, photo-ethnography was used to examine what health care access means for seafarers through the lens of structural violence. The study site was the vessel the seafarers worked and lived on, which docked in the Gulf of Mexico once-a-week, flies a flag of convenience, and travels in international waters. The photo-ethnography was implemented over a one-year period and included male Filipino seafarers who worked 9-month contracts at sea. The historical, structural, and political-economic production of injury, illness, and death were questioned to understand why migrant seafarers do not have de facto access to their de jure health rights. In this way, health prevention was analyzed through the discourse of power distribution instead of risk and disease. Results from the project reveal that seafarers routinely underreport adverse work and health conditions for fear of losing future work contracts. Adverse work experiences included dangerous vessels and routes as well as being encouraged to work with little sleep or through storms. Adverse health issues included severe to moderate injury and illness, which they concealed from management. Ultimately, it was revealed that political-economic systems are internalized and embodied among migrant workers who are employed under short-term contracts, leading to decreased healthcare-seeking behaviors and increased health disparities.